Træhuse fra Aalborg 1050-1600 – Planløsninger og indretninger - Klinge, Christian (Kuml, 2013)
The layout and organisation of wooden houses in Aalborg from 1050-1600 This analysis of the layout, organisation and use of wooden houses in Aalborg in the period 1050-1600 is based on the remains of 39 buildings from a total of 11 different excavations carried out between 1962 and 2008. Wooden houses have been excavated at 41 sites in Aalborg, but at only 12 of these sites was the level of recording adequate to permit inclusion in this analysis. In addition, Aalborg has 23 half-timbered houses dated prior to 1600, seven of which still stand on their original site. Out of this total of 62 wooden houses, 25 examples provide good information on layout, organisation and use and therefore form the backbone of this study. In terms of date, the main weight of the excavated houses lies in the 15th century, while the 14th century is poorest represented. Looking exclusively at the 23 best-preserved houses, the distribution is more uniform throughout the Middle Ages; however the 14th century remains underrepresented (tables 1 and 2). None of the houses in the present assemblage has been excavated in its full extent. Even so, it is apparent from the data that the width of the houses was very uniform: generally 5-6 m in the case of the excavated houses. The reason for this is probably that wider houses would require longer tie beams and thereby have a weaker construction. The houses were probably built with a framed construction that contained insufficient timber to stabilise a wider structure. The length of the houses varied as the timber-framed buildings have a modular construction made up of bays. The length of a house can therefore be increased as required by simply adding further bays. Regionality is a major question in the discussion of layout, organisation and use and as all the primary material for this study derives from Aalborg, it is possibly only representative of the situation in Northern Jutland. Studies of 18th century farmhouses show that regional differences do not necessarily follow the usual regional groupings and, moreover, that they can be quite considerable (fig. 4). Variation between houses can also be the result of the different housing requirements of the various social strata. If the study’s best preserved houses are examined in the light of the above, three things become immediately apparent: All the houses, with only two exceptions, are situated with their gable extending all the way out to the street, and secondly, also with two exceptions, they are located along Aalborg’s main thoroughfare. Finally, all the houses lie in a dense, intensive settlement. Despite the small sample size, the material reveals so many similarities between the houses that it can be considered to be homogeneous. Consequently, it is able to shed light on the prevailing conditions in the gable-fronted houses which faced on to Aalborg’s main street. A collective overview of the layout and organisation of the houses is best illustrated by figures 2 and 3, where the house outlines are arranged in chronological order. As is apparent, partition walls have exclusively been identified running across the houses, and the number of rooms in each of them is modest. In the houses dating from the period 1050-1300 it was apparently normal to have a large room out towards the street, and in several instances the presence of some form of hearth has been demonstrated here. The room behind this was generally slightly smaller or of the same size as that at the front. The houses from the period 1350-1600 are, as in the preceding period, very uniform. They all have a large room out towards the street, but it is not possible to demonstrate whether this room was heated. The most striking common feature of the houses is that there are hearth structures in the rearmost or middle room; these are interpreted as representing the kitchen regions in the houses. The layout and organisation of two of the timbered-framed houses match that of the two latest, excavated houses. In both cases there is a large room out towards the street; this room was heated by a jamb stove. Behind this room lies the room with the kitchen hearth arrangement. In general, it can be said that the layout of Aalborg’s medieval and early Renaissance town houses was not particularly complicated and there were only very few rooms. The differences between the two periods 1050-1350 and 1350-1600 lie primarily in where and how the hearth was situated in the house. The presence of fixed hearths can be relatively easy to demonstrate archaeologically, because charcoal and burnt clay are durable materials. Out of the 39 houses that were examined, a fixed hearth was not identified in only 12 cases, and of these houses without a recognised hearth, most had been only partially excavated. The evidence suggests that throughout the entire Middle Ages in Aalborg it was usual to employ stoves and open hearths side by side. This is in direct conflict with the accepted view that hearths were replaced by stoves during the course of the Middle Ages. It is not possible to ascertain whether this variation results from regional differences or a statistically inadequate sample (tables 3 and 4). If a stove is sited with the stokehole in one room and the stove chamber in the next, it becomes possible to heat a room without it being plagued by smoke (fig. 5). Some of Denmark’s earliest examples of jamb stoves were found in Aalborg and the two best examples were excavated at Algade 9. The two houses in question have been dendrochronologically dated to the 1120s (fig. 6) and the 1170s (fig. 7), respectively. One of them, house 8, was a direct replacement of the other, house 5. Both are well-documented with unequivocal traces of partition walls. The jamb stove heated the second room back from the street which, as a consequence, was warm and comfortable without the inconvenience of smoke. All the other hearths were located in the first room out to the street and activities which required a hearth must necessarily have taken place here. This way of organising the dwelling must, on the basis of the material analysed here, have been usual in the Early Middle Ages, up until the 14th century. Of the 15 houses dated to this period, the same pattern can be recognised, more or less, in eight of them. Probably the earliest house with a jamb stove was excavated at Bredgade 7 (fig. 2, house 2) and is dated stratigraphically to the end of the 11th century. In none of these Early Medieval jamb stoves has it been possible to demonstrate the use of “potkakler” – hollow ceramic tiles – in the stove construction. These tiles first appeared in Aalborg in the 15th century. Consequently, there is no connection between the introduction of “potkakler” and the introduction of jamb stoves to Aalborg. The evidence suggests that hearths after the 14th century, compared with the preceding period, were positioned further back in the house. The most marked traces of hearths are now to be found in the middle part of the house, corresponding to the second room in from the street. In houses 18, 20, 21, 22 and 23 on figure 3 there are complicated hearth structures which are, in all cases, interpreted as kitchen facilities (fig. 8). Consequently, the kitchen moved back in the house and it seems that this change took place after the middle of the 14th century. The position of the hearths in the two timber-framed houses 24 and 25 is almost identical to that seen in the houses from the Late Middle Ages. The kitchen hearth was located in the second room back from the street and was built up against the partition wall. The front room could thereby be heated with a jamb stove with a stokehole in the kitchen. This resulted in a heated but smoke-free room. In the two well-preserved houses 5 and 8, the presence of a door has been demonstrated between the front two rooms in the buildings, interpreted as the living quarters in the houses. As these buildings were gable-fronted houses, the main door must have opened to the street and access to the house’s second room, the one with the jamb stove, was therefore through the front room. This front room with the hearths was probably the most public room in the house. There are no traces of doors in the part containing the living quarters in the Late Medieval houses, but in the two timber-framed houses, a main door in the gable leads into the front room. This room was probably a more public room than the kitchen room behind it. There was direct access between the two rooms. In both houses, the kitchen room has a further outer door which must be perceived as a back door. In Denmark, fixed, raised wall benches are considered to be a completely standard fixture in the dwelling houses of Viking times and the Middle Ages. Their use ceased in Denmark during the course of the 13th century, a development which can be partially confirmed by the evidence from Aalborg. The wall benches probably went out of use because this was the time when movable furniture became more widespread. The excavated remains of the wooden houses in Aalborg demonstrate that, in the course of the Middle Ages, a change took place in the internal organisation of the houses. The main development was that the cooking hearth was moved from the front room further back in the house. As a consequence, cooking no longer took place in the first room encountered on entering the building. In the Early Middle Ages, a relatively standard pattern can be observed in the internal organisation of houses in Aalborg. At the front of the house, out towards the street, there was a room which contained all the house’s hearths. It was also from here that a jamb stove was fired, which heated the room behind. The smoke-filled front room would have been the first room people came into in the house, while the room behind would have been smoke-free. This latter, more comfortable room probably functioned as the house’s living-/bedroom. The fact that it was necessary to go through the first room in order to reach the more comfortable room behind suggests that the rear room was more private than that at the front. The room with the hearths was probably the place where externally-directed activities such as trade took place. In the excavated houses from the Late Middle Ages, the kitchen region is no longer found to be in the room out towards the street. It is unclear how the front room was used, but one possibility is that it had the same function as in the later timber-framed houses, i.e. as an entrance hall with externally-directed functions. The activities which took place around the house’s main hearth had possibly become of a more private nature and were therefore, together with the hearth, moved away from the front, more public, room. This change in internal organisation appears to have taken place during the course of the 14th century. If this is true, then it coincided with a series of other social changes and upheavals such as the agricultural crisis, the population decline, the plague epidemics and consequent changes in family structure. It is not inconceivable that the reason for the revised preferences with regard to specific types of dwelling organisation has its basis in these altered family patterns. The Late Medieval way of organising a dwelling next underwent changes at the beginning of the 17th century. Christian G. Klinge Nordjyllands Historiske Museum